The paired‐related homeobox protein 1 promotes cardiac fibrosis via the Twist1‐Prrx1‐tenascin‐C loop. (23rd October 2022) - Wang, Fengyuan; Zhao, Hongyi; Yin, Lin; Zhang, Wei; Tang, Yanhong; Wang, Xi; Huang, Congxin
Abstract: Cardiac fibrosis is a common pathology in the advanced stage of cardiovascular diseases, which leads to cardiac systolic and diastolic dysfunction. It is important to prevent cardiac fibrosis during myocardial injury. The transcription factor Prrx1 is involved in cancer‐associated fibrosis and other organ fibrosis. However, the role and mechanism of Prrx1 in cardiac fibrosis deserves further exploration. We identified that overexpressed Prrx1 promoted the proliferation and migration of cardiac fibroblasts, and transform cardiac fibroblasts to myofibroblasts in vitro. We demonstrated that the expression of Prrx1 is upregulated in TGF‐β1‐treated fibroblasts. And silencing Prrx1 could attenuate cardiac fibrosis induced by TGF‐β1 in vitro. In addition, a Twist1‐paired‐related homeobox 1 (Prrx1)‐tenascin‐C (TNC) positive feedback loop (PFL) combined with Twist1, Prrx1, and TNC activated fibroblasts, which was the mechanism the Prrx1 in cardiac fibrosis. In conclusion, our findings showed that the deficiency of Prrx1 attenuated cardiac fibrosis in vitro and reveal a novel Twist1‐Prrx1‐TNC PFL in the regulation of cardiac fibrosis.